Multiscale modeling of the hydromechanical behavior of fractured reservoirs - Rios, Ana Carolina Loyola Caetano (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Civil e Ambiental, 2022.